DSM-5: The intersectionality of spirituality, culture, and aging. Issue 1 (2nd January 2017) - Harris, Helen; Ellor, James W.; Yancey, Gaynor
ABSTRACT: Counselors practice with older adults whose religion and spirituality may be factors in assessment and treatment. The DSM-5 includes religion and spirituality as part of pathology or culture. This approach is supported in counselor education. Religion as a cultural derivative only reflects the human aspect of religion, not including a client's perception of divine actions possibly beyond the human experience, i.e., a miracle. How does the clinician discern if a client's experience reflects pathology or the possibility of some sort of miracle? This article includes strengths and limitations of a cultural definition of religious and spiritual experience with case applications.